Total laparoscopic hysterectomy: an experience at a tertiary care hospital - Rentiya, Fatma M.; Desai, Ajesh N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study is aimed to review indications, demographic data of patients, clinical outcomes and safety of total laparoscopic hysterectomy. Methods: This is a prospective observational study of total 150 patients who underwent total laparoscopic hysterectomy (TLH) from 1st June 2017 to 30th November 2018 in GMERS Civil Hospital Sola. Results: ~45% patients were between 40-50 years age group; 60% patients had 2 or more deliveries; commonest indication was symptomatic adenomyosis ; uterine size in ~57% of patients were up to 6 weeks; duration of surgery in ~91% of patients <120 minutes; intraoperative blood loss in all cases <200ml; no intra-operative and postoperative complications were encountered. Conclusions: TLH is safe procedure with minimal blood loss, minimal postoperative pain and discomfort and shorter duration of hospital stay when performed via expert hands.